JENIS TUMBUHAN DAN TIPE HABITAT DI HUTAN DATARAN RENDAH HAYA, MAMBERAMO, PAPUA - Marthen Jitmau; Amon A Rumbino (VOGELKOP: Jurnal Biologi, 2018)
ABSTRACTMamberamo lowland areas are generally contains of primary rainforests. Until now, basic research needs to documentation all of biology resourches because of many other important genetic data, evolution, and their implication to conservation management are not realy know. On the other hand, the development of new regency (Daerah Otonom Baru or DOB) still available to certain habitat use. The purpose of this study is to analyse habitat diversity, and identify plant species scattered in lowland forests around the Haya village, Mamberamo. Total 123 species (40 of family) of plants were found in Haya. We found there are two families of plant with highly dominant spescies in this region i.e. Arecaceae with 12 species or 9.75%, and 11 species of Moraceae (8.9%) are dominant of famili of plant found in this region. There are tree type of habitat at Haya i.e. plains, hills and seasionally inundeted.  ABSTRAKDataran rendah Mamberamo pada umumnya masih berupa hutan primer dan belum diteliti secara menyeluruh. Saat ini, masih diperlukan penelitian dasar untuk mendokumentasikan seluruh sumberdaya biologi karena banyak data penting genetik, evolusi dan implikasinya terhadap manajemen pelestarian belum diketahui secara pasti. Disisi lain, pemekaran wilayah DOB masih terus tersedia untuk menggunakan habitat tertentu. Tujuan penelitian ini adalah menganalisa keragaman habitat, dan mengidentifikasi spesies tumbuhan yang tersebar di hutan dataran rendah sekitar kampung Haya, Mamberamo. Total 123 spesies (40 famili) tumbuhan ditemukan di hutan dataran rendah Haya, Mamberamo. Famili dengan jumlah spesies terbanyak adalah Arecaceae 12 spesies (9.75%) dan 11 spesies Moraceae (8.9%). Terdapat tiga tipe habitat di Haya yaitu dataran rendah (plains), perbukitan rendah (hills), area yang secara musiman tergenang air (seasionally inundeted).